Pioglitazone therapy in progressive differentiated thyroid carcinoma - Rosenbaum-Krumme, S. J.; Bockisch, A.; Nagarajah, J. (Nuklearmedizin - NuclearMedicine, 2012)
Aim: Rosiglitazone achieved promising results in progressive differentiated thyroid carcinoma (DTC) with redifferentiative and antiproliferative effects, but has been taken off the market. Thus we evaluated another glitazone, pioglitazone, expecting similar positive results. Patient, materials, methods: Five patients with progressive DTC and no or only negligible iodine uptake were enrolled. Oral pioglitazone treatment was applied for 6 months. The re-differentiative effect was assessed by 124I-NaI PET/CT dosimetry and the anti-proliferative effect by 18F-FDG PET/CT imaging. Results: A redifferentiative effect of pioglitazone could not be shown. Lesion dosimetry indicated that 3/5 patients had unchanged no lesion absorbed dose per administered activity (LDpA) in any tumour lesion, 2/5 patients had a deterioration of LDpA within some lesions, thus radioiodine therapy was not performed in any patient. Volumetric analysis, using RECIST criteria, revealed progressive disease in 3/5 patients and stable disease in 2/5 patients. Metabolic changes, using EORTC criteria, revealed 3/5 patients with progressive metabolic disease, 1/5 patient with stable metabolic disease and 1/5 patients with partial metabolic response. The medication was well-tolerated, and no patient developed clinically important toxicity associated with the treatment. Conclusion: Pioglitazone revealed some positive effects in radioiodine negative and progressive DTC patients but it did not fulfill the expectations given by the results of rosiglitazone therapy.
Keywords: Re-differentiation; pioglitazone; thyroid cancer; 124I-Na; 18F-FDG; PET/CT